Growth Performance of Rabbits using Different Methods of Weaning Group Formation - Sitar, Nejc; Škorjanc, Dejan; Prevolšek Povše, Maja; Skok, Janko (Agricultura Scientia, 2026)
In rabbit meat production, weaning is a crucial phase and must be conducted properly to achieve adequate growth performance and slaughter weight in the shortest possible time. Studies on rabbit weaning, particularly concerning weaning methods (i.e. different approaches to forming weaning groups) and their effects on production, are scarce. Our study compared three weaning methods in indoor and outdoor breeding environment. In our experiment, rabbits were weaned by body size (same size together; n = 27), by litter of origin (littermates together; n = 30) or at random (n = 57). All rabbits were housed in wire cages in groups of three. Body weight, daily weight gain and feed conversion rate (FCR) were monitored over a period of 8 weeks from weaning to slaughter. The breeding environment and weaning methods affected most of the parameters, yet the interaction between the studied effects was insignificant during the entire experimental period. With the body size-based and random method, the rabbits reached significantly higher final body weight (2348 g and 2263 g, respectively) than rabbits weaned with the litter-based method (2168 g). Similarly, daily weight gain was 27.2 g, 25.7 g and 24.0 g (p = 0.024) for rabbits weaned using the body size-based, random and litter-based methods, respectively. Regarding the effects of the breeding environment, indoor housing provided better production results. The rabbits kept indoors grew faster than the outdoor rabbits (27.2 g/day and 24.1 g/day, respectively; p < 0.001) and had a 15% higher final weight (2345 g indoors, 2174 g outdoors, p < 0.001). Feed conversion ratio was lower (p < 0.001) in the indoor housing (≈2.5) than in the outdoor housing (≈3.0). However, the body size-based weaning method was found to be the most efficient for growth performance and final body weight, regardless of environment (indoor or outdoor). Randomly formed weaning groups or those formed from littermates performed better indoors; however, the latter (i.e. from littermates) anyway remained inferior to rabbits from the other two groups. The study therefore showed that the approach to weaning group formation and the environment crucially influence the efficiency of rabbit weaner fattening and should be considered by breeders when weaning kits.